The Czech Republic Sugar Market Development in the Context of the Phasing out of Sugar Quota - Kateřina Kovářová; Martin Nádeník; Kamil Pícha (DETUROPE)
The aim of the paper is to assess the current position and situation of the Czech sugar market actors. The new situation is expected due to the declared phasing of out of sugar quota with the EU Common Agriculture Policy. The analysis is based on secondary date from the statistics of the Czech Statistical Office and the Ministry of Agriculture of the Czech Republic. Czech Republic has a long strong tradition in sugar production. It lost a leading position in the sugar market in the past. The sugar industry has been affected by various factors during several periods. The last big challenge for the market was the restricting system of the Common Agriculture Policy of the European Union. The expected development of the sugar market in the no-quota environment could be a good opportunity for both Czech sugar beet producers and sugar beet manufacturers (sugar producers).